History of controlled trials in medicine: real priorities are little-known. Report 3. Quasi-randomized and randomized trials in humans and animals - A. N. Koterov; O. A. Tikhonova; L. N. Ushenkova; A. P. Biryukov (IRBIS LLC, 2022)
The three-report review is aimed to describe the historical development of clinical trials, controlled trials (CT) and randomized controlled trials (RCT), and the inclusion of these approaches in health-related disciplines (Medicine and Epidemiology). Report 3 summarizes historical milestones (ideas and studies) for quasi-randomized CT ('alternate allocation'; 88 milestones) and RCT (37 milestones). It was found that although the ideas of both designs are a thing of the past (from A. Lesassier Hamilton (1816) and J.B. Van Helmont (1648), respectively), the bulk of the tests were carried out in the 20th century, when both designs existed in parallel. Overall, the alternate allocation was used nearly three times longer than randomization.Analysis of the sources showed that the first RCT in medicine was the work of D. Colebrook, 1925 (Great Britain), and the first close to the modern RCT, including randomization according to the table of random numbers, was J.A. Bell, 1941 (USA). Often referred to as the 'new era in CT' and 'the origine of RCT', a study of the effects of streptomycin on tuberculosis in 1946-1948, which was also designed by A.B. Hill is only 13th known RCT, only 9th RCT in medicine and only the 2nd with modern randomization. Other facts of insufficient reflection of the priorities and real history of CT/RCT in West and Russian publications were found, including dozens of Western textbooks on epidemiology and evidence-based medicine of recent decades. True priorities are often omitted, and the most frequent references to the history of CT (progressively) are the experience of the prophet Daniel, the experience of the surgeon J. Lind, and the study on the effect of streptomycin on tuberculosis in 1946-1948.Based on a PubMed/MEDLINE search, a summary of alternate allocation CT, and RCT for the period 1960-1990 to 2020 is provided. In the first case, single publications were found, but the fact that design with alternation survives to this day is important. For RCT, since 1990s, an increase in the number of papers (up to tens of thousands per year) has been revealed. The data are given for the total number of RCTs performed by countries, continents and parts of the world for 2020. According to the calculated index of the ratio of the number of RCTs to the specific number of doctors (per 100,000 population) among 45 countries of Eurasia (from France to Tajikistan), Russia ranks 12th.A three-report review based on the originals of nearly all publications from the late 19th century and including the necessary references and citations can serve as a reference guide to the historical development of CT and related topics.